Prevention and Control of Infectious Diseases Act 1988 [Act 342] Prevention and Control of Infectious Diseases (Measures within The Infected Local Areas) Regulations 2020 (P.U.(A) 91/2020) - Ali Mohamed, Ashgar Ali (LexisNexis, 2020)
This document purports to provide a section-by-section annotation of the Prevention and Control of Infectious Diseases (Measures Within the Infected Local Areas) Regulations 2020 and to address frequently asked questions that may arise therefrom.